THE IMPROVEMENT OF VERB TEACHING WITHIN ROMANIAN LANGUAGE FOR FOREIGNERS BY USING A VERB GUIDE - VESA-FLOREA, Viorica (Studia Universitatis Babeș-Bolyai Philologia, 2017)
The improvement of verb teaching within Romanian Language for Foreigners by using a verb guide. The work presents the need and utility to conceive a verb guide which would help the persons interested in learning Romanian as a foreign language and which would have as target-public not only the preparatory year students, but a wider range of public, meaning any person interested in developing the communication competence in this language in a practical, progressive way and in accordance with the concrete everyday communicative needs. The structure of such volume should comprise, besides the conjugation tables of the verbs grouped on levels, their translation in several wide-spread languages, their contextualization, summary tables with the verbs used with the Dative, and also models of their prepositional status, this means just the aspects in which the foreign speakers have difficulties. Another perspective for selection and contextualisation of the verbs could be their belonging to a certain semantic sphere, a modality to concentrate, simplify and stimulate the individual and collective progress, reflected in the different competences. Rezumat. Îmbunătățirea predării verbului în cadrul L.R.S. prin folosirea unui ghid de verbe. Lucrarea prezintă necesitatea și utilitatea conceperii unui ghid de verbe care să vină în ajutorul celor interesați de însușirea limbii române ca limbă străină și care să aibă ca public-țintă nu doar studenții din anul pregătitor, ci o paletă mai largă a publicului, adică orice persoană interesată să-și dezvolte competența de comunicare în această limbă în mod practic, progresiv și în acord cu necesitățile concrete comunicative cotidiene. Structura unui asemenea volum ar trebui să cuprindă, pe lângă tabelele de conjugare ale verbelor grupate pe niveluri, traducerea lor în câteva limbi de circulație, contextualizări ale acestora, tabele recapitulative cu verbele care cer Dativul, precum și modele ale regimului prepozițional ale acestora, adică tocmai aspectele în care aceștia au dificultăți. O altă perspectivă de selectarea și contextualizare a verbelor ar putea fi apartenența acestora la o anumită sferă semantică, modalitate de a concentra, simplifica și stimula progresul individual și colectiv, reflectat în diferitele competențe. Cuvinte cheie: româna ca limbă străină, ghid de verbe, contextualizări, metode practice, dificultăți.